Pengaruh Model Pembelajaran Project Based Learning Terhadap Kemampuan Menulis Naskah Drama Kelas XI Madrasah Aliyah Mathla’ul Anwar Pusat Menes - Nanang Maulana; Aminah Aminah (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2026)
The research entitled "The Influence of the Project Based Learning Learning Model on the Ability to Write Dramatic Manuscripts for Class XI Madrasah Aliyah Mathla'ul Anwar Pusat Menes" aims to find or determine the effect of the Project Based Learning model on the ability to write drama scripts. In this study, the authors used a quantitative approach with a type of experiment with research techniques used including literature review, trials, analytical techniques, test techniques or assessments. From the results of the research conducted, there was an effect of using the Project Based Learning learning model on the ability to write drama scripts for class XI Madrasah Aliyah Mathla'ul Anwar Pusat Menes. Based on the calculations, it is obtained that t count is 6.754 and t table is 1.661 with a significance level of α = 0.05 and degrees of freedom 66. The value of t count > from t table, then based on the criteria for testing the hypothesis H0 is rejected and H1 is accepted. This means that there is a significant effect of using the Project Based Learning learning model on the ability to write drama scripts, the results are higher when compared to using the direct learning model.